Seasonal variation of live weight in Criollo bucks, in Southern Mendoza (Veterinary Science, 2019)
The objective of the present study was to evaluate the variation ofthe live weight of Creole goats males studied within the Castron Planat the beginning and at the end of the service period, in the South ofMendoza. For that purpose, 824 Creole type males, divided accordingto age by dental chronology, were used. Live weight was evaluated withan electronic scale of 150 kg maximum capacity, with 50g of precision,in May (austral autumn), at the beginning of the reproductive stageand in September (austral spring), at the time that the goats were removedfrom the producing establishments by “the castronero”. Theexperimental design responded to a completely randomized model,evaluating standard means and deviations between the differentwork moments by Tukey test applying the statistical program InfoStat2.0. The results showed 28.13 weights±4.4 and 27.94±5.1 kg for maleswith 2 teeth, in September, and autumn respectively; 52.35 ± 4.7 and41, 92±7,4 kg for males with 4 teeth, males 68.4 ± 6.3 and 56.7 ±6 , 7kg for the goats with 6 teeth, 78,84 ± 6.2 and 62, 3±7, 6 kg for maleswith full mouth and 70.4 ±6, 9 and 57.4 ±7 , 3 kg for the goats with halftooth, there is a significant statistical difference (p≤0. 05) between thetwo periods evaluated for animals 4-6 teeth, mouth full and half tooth.We conclude showing the live weight of the selected Creole goatsin Plan Castron a significant seasonal variation between the onset ofthe reproductive season (austral autumn) and the end of the servicestage (austral spring) influenced by the condition of the natural grasslandfor every moment and the males´ activity during the reproductiveseason
Keywords: criollo goats; male; live weight; seasonal variation